Andira Watson in The Key of Friendship and Poetry with Shirley Campbell: “Sorority” Between Afro-Caribbean Poets - Chen Sham, Jorge (2020)
What happens when a poet publicly dedicates a poem to another poet? This article answers this question by reviewing the classic tradition that, from an awareness of a fraternity between “soul mates”, makes the exchange of affections and feelings the expression of shared aspirations. Carrying out a public dedication highlights ideological and stylistic ties to create a political and ethical agenda. Nicaraguan poet Andira Watson does this by making a public tribute to her Costa Rican colleague Shirley Campbell. It is a context in which the Afro-Caribbean identity is highlighted in order to demonstrate her assumed and vindicated “sorority”.